Effects of needle inner surface topography on friction and biopsy length. (December 2016) - Li, Weisi; Zhou, Ping; Lin, Wei-Chen; Nteziyaremye, Valens; Yamaguchi, Hitomi; Guo, Dongming; Shih, Albert
Abstract: The effects of inner surface topography on friction force and the coefficient of friction between an inner surface of needle and tissue phantom during needle insertion and on biopsy length are examined using polished, and unpolished needles. In this paper, the inner surfaces of the needles are altered by magnetic abrasive finishing (MAF), and the needle inner surfaces were smoothed from 0.43 to 0.02 µm Sa (referred to as the smoothly polished needle ) or 0.26 µm Sa (referred to as the roughly polished needle ). With polyvinyl chloride (PVC) as a tissue-mimicking phantom material, the smoothly polished needle results in the smallest inner friction force (0.0024 N/mm), the smallest coefficient of friction (0.35), and the longest biopsy length (34.3 mm). The roughly polished needle produces the largest inner friction force (0.0041 N/mm), the largest coefficient of friction (0.56), and the shortest biopsy length (30.5 mm). Although the inner surface roughness of the roughly polished needle is lower than that of the unpolished needle, the inner friction force and coefficient of friction are larger than those of the unpolished needle. This may be caused by the ridges and grooves in the circumferential direction of the roughly polished needle made with MAF. Based on the surface topography data, the ratchet mechanism is utilized to calculate the coefficient of friction. The results suggest a higher coefficient of friction in the roughly polished needle. The biopsy tests also show the shortest biopsy sample is extracted using the roughly polished needles, which exhibit the greatest inner friction force. Graphical abstract: Highlights: Needle inner surfaces were smoothly (0.02 µm) and roughly polished (0.26 µm) by MAF. Smoothly polished needle had lowest inner friction force and largest biopsy length. Roughly polishing reduced Sa but increased inner friction force. Inner surface topography direction affected the needle inner friction force. Smaller inner friction force leads to larger biopsy length.